Revisiting the epidemiology of mid shaft clavicle fracture-recent and emerging trends - Belapurkar, Kaustubh (International Journal of Research in Orthopaedics, 2022)
Background: Clavicle fracture is a common injury involving upper limb. It accounts for 2.6-5% of injuries. Most common mechanism causing this injury is a fall on an outstretched hand. Clavicle fractures have a bimodal distribution with 1st peak in young active adult males less than 30 years of age. Second peak in elderly females with osteoporotic bones. The annual incidence is highest in male under 20 age group, decreasing with subsequent age groups. Road traffic accidents is another mode of injury which is becoming increasingly common for mid shaft clavicle fractures. Methods: A prospective study was carried out over 12 months. A total of 126 patients met the inclusion criteria. The epidemiological data was collected at the time of presentation using standard case sheet proforma. Radiographic assessment was done for fracture classification. Results: Mid Shaft clavicle fracture was most common in middle aged males (31-40 years) with right side being most commonly affected. Road traffic accidents was the most common cause of injury (62%). AO/OTA type 15B1 is the most common fracture morphology (45%). Most of the high energy road traffic accidents are associated with 15B3 type fractures while type 15B1 is more common in low energy mechanisms like ground level fall. Conclusions: Mid shaft clavicle fracture is a common injury in young population. It is increasingly being associated with road traffic accidents. The number of comminuted fractures, which represent high energy injury mechanism has been on the rise due to increase in high velocity accidents.